Sofi Oksasen romaanitaide Kertomus, etiikka, retoriikka - Lehtimäki, Markku (Suomalaisen Kirjallisuuden Seuran Toimituksia, 2022)
Sofi Oksanen is the most visible and widely discussed Finnish author of the 21st century, yet her novels have gained less attention than her public performances. This study shifts the focus from the author's persona to her literary art, proposing to read Oksanen's fiction from the methodological viewpoint of the rhetorical theory of narrative. Accordingly, Oksanen's six novels published to date - Stalinin lehmät, Baby Jane, Puhdistus, Kun kyyhkyset katosivat, Norma, and Koirapuisto - are considered as examples of authorial rhetoric and ethics, as narrative and textual constructions, and as affective readerly experiences. Instead of only following the rhetorical theory's emphasis on character, plot, and progression, however, the study develops a new kind of narrative rhetoric, which also pays attention to language and politics. In the study, Sofi Oksanen emerges as a feminist narrative artist, who employs fiction as a serious rhetorical resource in order to say something worthwhile about the past history as well as the contemporary world.